Portrait of 8 National Education Quality Standards Through the Implementation of Internal Management Audits at SDN 04 Wonokerto - Solhan, Ahmad; Imron, Ali (Proceedings Series of Educational Studies, 2024)
This study aims to examine the portrait of 8 educational quality standards through internal audit of school management at SD Negeri 04 Wonokerto. The type of research used is explanatory case study research. Several things examined are 8 educational qualities, which are mapped through (1) the condition of the school's vision and mission, (2) the condition of target standards and achievement strategies, (3) the condition of leadership actualization, management systems, and quality assurance systems, (4) the condition of student affairs and graduate output, (5) the condition of human resource management, (6) the condition of curriculum, learning, and academic atmosphere, (7) the condition of school financing, facilities and infrastructure and information systems, (8) the condition of PTK implementation and external cooperation. The results of the study SD Negeri Wonokerto 04 is an integrated school that is able to run various standards in it optimally in accordance with the existing foundations, both legal and theoretical. then the unique and quality thing at SDN 04 Wonokerto is the implementation of curriculum and student management based on e-reports for distributing grades to students.